Characterisation of chemical properties of the produced organic fractions via hydrothermal liquefaction of biosolids from a wastewater treatment plant. (March 2023) - Al-juboori, Jasim M.; Lewis, David M.; Hall, Tony; van Eyk, Philip J.
Abstract: Upgradable renewable crude oil produced from the hydrothermal liquefaction (HTL) of municipal wastewater sludge (biosolids) has the potential to be a sustainable feedstock to produce renewable crude oil. A range of biosolids with different organic fractions was tested under controlled HTL operating conditions to quantify the composition of the produced renewable crude oil. The HTL results demonstrated that both the HTL reaction conditions and biosolids composition have significant effects on the chemical properties of the produced renewable crude oil. Gas chromatography-mass spectrometry (GC-MS) identified a complex mixture of >300 major compounds in the produced renewable crude oil. The predominant components identified from the lipid, protein, carbohydrate and lignin constituents were cyclic terpanes and terpenes, along with nitrogenous, oxygenated, and phenolic components. Based on the boiling point of the produced compounds, high gasoline and naphtha-like and high diesel-like yields were produced from biosolid samples with high lipid and protein content, while the kerosene-like best yield was generated from a high lipid sample. A significant gas oil-like yield was produced from the high lipid and carbohydrate biosolid samples, while a high-yield of wax, lubricating oil and vacuum gas oil-like contents were generated from the high lignin sample. Highlights: Developing and modifying methods were essential to analysis biosolids composition. Boiling point profiles of renewable crude determined by Gas Chromatography analysis. The pathway of HTL involves de-polymerization, de-composition and recombination.